Burden of Ischemic Heart Disease and Its Attributable Risk Factors in North Africa and the Middle East, 1990 to 2019: Results From the GBD Study 2019 - Arya Aminorroaya; Sahar Saeedi Moghaddam; Hamed Tavolinejad; Zahra Aryan; Behnam Heidari; Hedyeh Ebrahimi; Mohammadreza Naderian; Parnian Shobeiri; Ali Ghanbari; Nazila Rezaei; Mohammad‐Reza Malekpour; Rosa Haghshenas; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The North Africa and Middle East (NAME) region has one of the highest burdens of ischemic heart disease (IHD) worldwide. This study reports the contemporary epidemiology of IHD in NAME. Methods and Results We estimated the incidence, prevalence, deaths, years of life lost, years lived with disability, disability‐adjusted life years (DALYs), and premature mortality of IHD, and its attributable risk factors in NAME from 1990 to 2019 using the results of the GBD (Global Burden of Disease study 2019). In 2019, 0.8 million lives and 18.0 million DALYs were lost due to IHD in NAME. From 1990 to 2019, the age‐standardized DALY rate of IHD significantly decreased by 33.3%, mostly due to the reduction of years of life lost rather than years lived with disability. In 2019, the proportion of premature death attributable to IHD was higher in NAME compared with global measures: 26.8% versus 16.9% for women and 18.4% versus 14.8% for men, respectively. The age‐standardized DALY rate of IHD attributed to metabolic risks, behavioral risks, and environmental/occupational risks significantly decreased by 28.7%, 37.8%, and 36.4%, respectively. Dietary risk factors, high systolic blood pressure, and high low‐density lipoprotein cholesterol were the top 3 risks contributing to the IHD burden in most countries of NAME in 2019. Conclusions In 2019, IHD was the leading cause of death and lost DALYs in NAME, where premature death due to IHD was greater than the global average. Despite the great reduction in the age‐standardized DALYs of IHD in NAME from 1990 to 2019, this region still had the second‐highest burden of IHD in 2019 globally.